Pengaruh Kualitas Pelayanan SIPRAJA, Citra Publik, dan Kepuasan terhadap Kepercayaan Warga dalam Pelayanan Administratif di Desa Tambaksumur - Widya Arliadinanti; Iswati Iswati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine the influence of SIPRAJA service quality, public image, and community satisfaction on public trust in administrative services at the Tambaksumur Village Government Office. The population consists of residents of Tambaksumur Village who have used the SIPRAJA application, a digital public service system developed by the Sidoarjo local government, to process domicile letters and other administrative documents. The research focuses on several key variables, including the quality of the SIPRAJA system, the public image of the Tambaksumur Village Government Office, citizen satisfaction, and the level of trust in the services provided. Additional aspects assessed include the functionality and usability of the application, the simplicity of operating the system, the quality of service delivered by administrative officers, and the comfort of the waiting room environment. Data were collected through questionnaires distributed to citizens who had experience using the SIPRAJA service. The analysis was conducted using descriptive methods and the Importance–Performance Matrix technique to evaluate how well the services meet community expectations and identify areas that require improvement to strengthen public trust in village administrative services.